PENGARUH KEGIATAN MELIPAT KERTAS TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI RA SABILISSALAM BAREGBEG CIAMIS - Puspiani, Dewi; Purbayani, Rini; Herniawati, Ani (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
This study aims to determine the influence of origami paper folding activities on early childhood's fine motor skill. In this study, the researchers used quantitative method under Pre-Experimental Design with the One Group Pretest-Posttest Design. The number of samples were 13 students with a saturated sampling technique. The data were collected using a structured observation sheet and processed by SPSS, then the testing hypothesis was carried out by using the Wilcoxon test. The results of the study showed that the early childhood's fine motor skill scores before given treatment were in the Not Yet Developed (BB) category with a percentage of 79.92% and 23.08% were in the Starting to Develop (MB) category. After giving treatment in the form of origami paper folding activities, it showed that 13 students, 69.23% were in the Developing According to Expectations (BSH) category and 30.76% were in the Very Well Developing (BSH) category. After carrying out the Wilcoxon test, it was found that the Aymp. Sig. (2-tailed) is 0.001 < 0.05. This showed that there was a significant difference between Pre-Test and Post-Test scores, at which the Sig value, (2-tailed) < 0.05 H1 is accepted. Thus, it can be concluded that paper folding activities influenced the early childhood's fine motor development at RA Sabilissalam.